Learning WCF - Bustamante, Michele Leroux (O'Reilly Media, 2007)
This easy-to-use introduction to Microsoft Windows Communication Foundation (WCF) is ideal for developers who want to learn to build services on a company network or as part of an enterprise system. Built into Windows Vista and Longhorn, and available for Windows XP and Windows 2003, WCF provides a platform for service-oriented architecture (SOA) that enables secure and reliable communication among systems within an organization or across the Internet. With WCF, software developers can focus on their business applications and not the plumbing required to connect them. Furthermore, with WCF developers can learn a single programming API to achieve results previously provided by ASMX, Enterprise Services and .NET Remoting. Learning WCF removes the complexity of using this platform by providing detailed answers, explanations and code samples for the most common questions asked by software developers. Windows Communication Foundation (or WCF, formerly code name "Indigo") provides a set of programming APIs that make it easy to build and consume secure, reliable, and transacted services. This platform removes the need for developers to learn different technologies such as ASMX, Enterprise Services and .NET Remoting, to distribute system functionality on a corporate network or over the Internet. The first truly service-oriented platform, WCF provides innovations that decouple service design and development from deployment and distribution - creating a more flexible and agile environment. WCF also encapsulates all of the latest web service standards for addressing, security, reliability and more